Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If $A,B$ non empty, upper bounded sets and $A+B=\{a+b\mid a\in A, b\in B\}$, how can I prove that $\sup(A+B)=\sup A+\sup B$?

share|improve this question
4  
The same way you show anything about a supremum: show that the right side is an upper bound of A+B, and then show that any other upper bound is larger. –  Nate Eldredge Sep 13 '10 at 17:25
    
If this is homework, tag it as such. –  lhf Oct 22 '10 at 10:23
add comment

4 Answers 4

up vote 10 down vote accepted

Show that $\sup(A+B)$ is less than or equal to $\sup(A)+\sup(B)$ by showing that the latter is an upper bound for $A+B$. Then show that $\sup(A)+\sup(B)$ is less than or equal to $\sup(A+B)$ by showing that $\sup(A+B)$ is an upper bound for $A+\sup(B)$ and that $\sup(A+\sup(B)) = \sup(A)+\sup(B)$.

share|improve this answer
    
Elegant way to do it, since unlike the other answer, it also works in the context of e.g. the natural numbers. –  cib Sep 5 '13 at 22:23
add comment

Set $x=\sup A$, $y=\sup B$. Given $a\in A, b\in B$ we have $a\le x, b\le y$ so $a+b\le x+y$ so it's an upper bound. Now take $\varepsilon > 0$ and find $a,b$ such that $a>x-\varepsilon/2, b>y-\varepsilon/2$ and you have $a+b > x+y - \varepsilon$. That suffices (since it means that every potential "smaller upper bound" $x+y-\varepsilon$ is not really an upper bound).

share|improve this answer
add comment

(question 2. http://webcache.googleusercontent.com/search?q=cache:DohoRC3-bU8J:www.maths.usyd.edu.au/u/UG/IM/MATH2962/r/PDF/tut01s.pdf)

The idea is to prove two inequalities: sup(A+B) ≥ supA+ supB and sup(A + B) ≤ supA + supB.

$\Large{Prove \; \sup A + \sup B \le \sup(A + B)}$:

By definition of A + B and sup(A + B), for all a ∈ A and b ∈ B, $\color{seagreen}{a + b} - b \quad \color{seagreen}{\le \quad \sup (A + B)} - b$

Hence if we fix $b ∈ B$, then $\color{seagreen}{\sup (A + B)} - b$ is an upper bound for $\color{seagreen}{A + B} - B = A$.

And so by definition of $\sup A$, for every $b ∈ B$, $\sup A ≤ \sup (A+ B) − b $.
Rearrange: $\color{magenta}{b} ≤ \sup(A +B) − \sup A$ for all $b ∈ B$.
Ergo, $\qquad \qquad \sup(A +B) − \sup A$ is an upper bound for any $\color{magenta}{b}$.

So again by the definition of a supremum: $\color{magenta}{\sup B} ≤ \sup(A + B) − \sup A \qquad \iff \sup A + \sup B ≤ \sup(A + B).$

$\Large{Prove \; \sup A + \sup B \ge \sup(A + B)}$:

Since sup A is an upper bound for A, $a ≤ \sup A$ for all a ∈ A.
Similarly, $b ≤ \sup B$ for all b ∈ B. Hence $a + b ≤ \sup A + \sup B$ for all x ∈ A and y ∈ B.
Ergo $\sup A + \sup B$ is an upper bound for A + B.
Hence by definition of a supremum, $\sup A + \sup B \ge \sup(A + B)$.

share|improve this answer
add comment

Another proof for $\sup(A + B) \ge \sup A + \sup B$.

$\Large{\sup A + \sup B \; is \; finite.}$

Posit $e > 0.$ Then there exists $a \in A$ and $b \in B$ such that $x > \sup A − \frac{e}{2}$ and $y > \sup B − \frac{e}{2}$. Then $a + b \in A + B$. Ergo $\color{seagreen}{sup(A + B)} \ge a + b \color{seagreen}{> \sup A + \sup B - e}$.
$\implies \color{seagreen }{ \sup(A + B) > \sup A + \sup B - e }$.
Since $e > 0$ is arbitrary, $\sup(A + B) \ge \sup A + \sup B$

$\Large{\sup A + \sup B \; is \; infinite.}$

enter image description here

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.